Comparative Transcriptome Analysis in Homo- and Hetero-Grafted Cucurbit Seedlings - Bantis, Filippos; Tsiolas, George; Mouchtaropoulou, Evangelia; Tsompanoglou, Ioanna; Polidoros, Alexios N.; Argiriou, Anagnostis; Koukounaras, Athanasios (Frontiers in Plant Science, 2021)
Watermelon (Citrullus lanatus) is a valuable horticultural crop with nutritional benefits grown worldwide. It is almost exclusively cultivated as grafted scions onto interspecific squash rootstock (Cucurbita maxima × Cucurbita moschata) to improve growth and yield and to address the problems of soilborne diseases and abiotic factors’ stress. This study aimed to examine the effect of grafting (homo- and hetero- grafting) on the transcriptome level of seedlings. Therefore, we compared homo-grafted watermelon (WW) to non-grafted watermelon control (W), homo-grafted squash (SS) to non-grafted squash control (S), hetero-grafted watermelon onto squash (WS) to homo-grafted squash (SS), and hetero-grafted watermelon onto squash (WS) to homo-grafted watermelon (WW). Different numbers of differentially expressed genes were identified in each comparison. In total, 318 significantly differentially expressed genes were detected between the transcriptomes of hetero-grafts and homo-grafts at 16 hours after grafting. Overall, significantly higher number of downregulated transcripts was detected among differentially expressed genes. Only one gene showing increased expression related to cytokinin synthesis was common in 3 out of 4 comparisons involving WS, SS and S. The highest number of differentially expressed transcripts (433) was detected in the comparison between SS and S, followed by 127 transcripts between WW and W. The study provides a description about the transcriptomic nature of homo- and hetero-grafted early responses, while the results provide a start point for the elucidation of the molecular mechanisms and candidate genes for functional analyses of hetero-graft and homo-graft systems in Cucurbitaceae and generally in plants.